Pengaruh Pemanfaatan E-Filing Sanksi Pajak dan Pengetahuan Wajib Pajak terhadap Kepatuhan SPT Tahunan Pelaporan - Riris Togi Marito Nadapdap; Albert Herlambang; Deliyanti Simbolon (Politeknik Ganesha Medan, 2026)
This study aims to analyze the effect of e-filing utilization, tax sanctions, and taxpayer knowledge on individual taxpayers’ compliance in reporting Annual Tax Returns at KPP Pratama Medan Barat, both partially and simultaneously. This research employs a quantitative approach using primary data collected through questionnaires distributed to respondents. The unit of analysis consists of individual taxpayers registered at KPP Pratama Medan Barat. The sampling technique used is incidental sampling, with a total sample size of 399 respondents.The analytical method applied in this study is multiple linear regression with the following equation: Annual Tax Return Compliance = 6.933 + 0.124 E-Filing Utilization + 0.186 Tax Sanctions + 0.276 Taxpayer Knowledge + e. The partial test results indicate that e-filing utilization, tax sanctions, and taxpayer knowledge each have a significant effect on Annual Tax Return compliance. This is evidenced by the t-statistics values exceeding the t-table values and significance levels below 0.05.Simultaneously, the results show that all independent variables collectively have a significant effect on Annual Tax Return compliance, as indicated by the F-statistic value exceeding the F-table value and a significance level below 0.05. Therefore, it can be concluded that e-filing utilization, tax sanctions, and taxpayer knowledge play an important role in improving individual taxpayer compliance in reporting Annual Tax Returns at KPP Pratama Medan Barat.